Pelatihan Aplikasi Perkantoran Bagi Perangkat Desa Dalam Upaya Peningkatan Kinerja Dan Pelayanan Prima - Hamonangan Kinantan Prabu; Yuni Widiastiwi; Iin Ernawati (Universitas Persada Indonesia YAI, 2023)
Rawa Panjang Village is one of the villages in the Citayam area, Bogor district. In this village there is abeautiful swamp that is produced into a tourist spot and fishing and community ponds. Problems found in thearea, namely the limited ability of village officials to use and operate IT-based applications used in providingservices to community needs, so that the services provided are still below the standard of excellent service.The solution that can be given as a step to anticipate and develop services is to provide training on the use ofIT-based office applications that are expected to improve the skills and knowledge of village officials, so asto improve service performance towards excellent service and provide satisfaction for the community. Thetarget output expected after the implementation of this IT-based office application training activity is anincrease in the ability and skills of village officials so as to improve performance and excellent service